Integrating Petrography With Core-Log-Well Test Data For Low Permeability Sandstone Reservoir Characterization: Preliminary Recommendation For Production Optimization - Junita Trivianty Musu; Hadi Prasetyo; Bambang Widarsono (Scientific Contributions Oil and Gas, 2010)
Integrating petrographic core information into combined core petrophysics, log, and well test data for understanding facies and environmental deposition in rock characterization has proved itself useful to improving quality and reliability of the required conclusions. This integrated approach has specifically shown its use in the cases of complex reservoirs such ones characterized as low-permeability sandstone reservoirs. It is in this spirit that this paper demonstrates how this virtually cost efficient analysis provides preliminary recommendations for the exploitation of such reservoirs. As case study, two types of producing reservoirs (Bekasap, Bangko, Pematang, and Tanjung Formations) have been taken in 2009. The first type is strongly controlled by depositional environment. It is found in the upper part of Bekasap and Bangko formations (1900 - 2300 ft-ss), deposited in estuarine system, and made of very fine to fine grained sand with low to moderate bioturbation. This mostly feldspathic and lithic greywackes have permeability of up to 200 mD. The second type is strongly dominated by diagenesis process and is mainly found in the Upper Pematang and Tanjung Formations (6200 - 7400 ft-ss). This reservoir type is characterized by its coarse-grained and conglomeratic sandstones resulted from fan- elta and braided channel depositional system. Diagenetic events such as compaction, recrystallization of matrix into microcrystalline clay minerals, precipitation of authigenic minerals in pore system are also well identified from the performed petrographic analysis. This is dominated by sublitharenite and litharenite sandstones exhibit horizontal permeability of up to several dozens mD. The two producing reservoir types have undergone carefully planned exploitation and stimulation operations, and the horizontal drilling and fracturing